A Participatory Truth Pedagogical Model Based on John 18:37 for Christian Religious Education in the Post-Truth Era - Fazar Yeshekiel Sinaga; Afrina Jeliyanti Sirait (Civiliza Publishing, Indonesia., 2026)
This study aims to develop a Participatory Truth Pedagogical Model based on Jesus' testimony in John 18:37 as a pedagogical response to the Post-Truth phenomenon in Christian Religious Education (CRE). The main problem addressed is the crisis of truth literacy among young Christians, where emotions and subjective opinions often override objective facts and biblical truth, rendering one-way doctrinal teaching models inadequate. This research employs a qualitative approach using comparative study and content analysis methods, comparing the concept of truth in the exegesis of John 18:37 with the characteristics of the Post-Truth phenomenon, then synthesizing them into an applicable pedagogical framework. The findings formulate the 4P-Participatory Model, consisting of four pillars: (1) Encounter through dialogical relationships with truth; (2) Deepening through critical thinking and digital literacy training; (3) Practice through actualizing truth in concrete actions; and (4) Mentoring within a reflective faith community. This model offers a holistic approach integrating the cognitive, affective, and psychomotor aspects of learners. The conclusion affirms that CRE in the Post-Truth era requires a paradigm shift from instructional-passive teaching toward participatory-dialogical pedagogy. This research recommends implementing this model in church and Sunday school curricula, as well as facilitator training to guide contextual and sustainable truth learning processes.